PENERAPAN CROSS FUNCTIONAL TRAINING DALAM MENINGKATKAN KEPERCAYAAN KEPALA DESA SEBAGI PEMBINA DI PAUD WIDYA KARYA - Al dhita Ika Putri Irianti; Rofik Jalal Rosyanafi; Gunarti Dwi Lestari; Wiwin Yulianingsih (MOTORIC, 2020)
This study aims to determine the application of Cross Functional Training as an effort to increase stakeholder confidence in this case the village head as an advisor in PAUD Widya Karya. Researchers are uneasy about the phenomenon of the lack of synergy between educators and PAUD Widya Karya's education staff and policy makers as well as coaches, in this case the Village Head. The method used in this research is qualitative with a case study approach. The subjects in this study were all HR in Widya Karya PAUD, in this case the teaching and educational staff. Data collection techniques used in this study include observations, interviews and documentation. The results of this study indicate that there is a significant increase in trust from village heads in the competence of teaching and educational staff as operators of early childhood education services in PAUD Widya Karya. This condition cannot be separated from Cross Functional which is implemented by all existing teaching and education staff. Villagers as costumers feel satisfied, especially for administrative services provided not only by educational staff but are often also provided by educators whose true focus is on the teaching dimension and not on the fulfillment of administrative services. Keywords: Cross Functional Training, Village Head Beliefs as Trustees